Pelatihan Pembuatan Laporan Keuangan Pada UMKM Kampung Madu Kabupaten Kediri - Purwanti, Lilik; Triyuwono, Iwan; Zuhrotin Nasyi’ah, Eny; Prakoso, Aryo (Madani : Indonesian Journal of Civil Society, 2024)
This community service activity by the Faculty of Economics and Business team of Universitas Brawijaya aims to share the knowledge and skills of MSME actors in conducting bookkeeping and preparing financial statement activities. This activity is very much needed because MSME activists still lack knowledge and skills in bookkeeping, preparing financial reports so that it is difficult to know the position of their business profit or loss. In addition, by having financial reports, MSMEs that experience obstacles in accessing financing or obtaining tax incentives can be resolved. The method of implementing this community service consists of socialization activities, training activities and evaluation for participating MSMEs. The activities were carried out for MSME players in Kampung Madu, Badas Village, Kediri Regency. The training covered topics such as financial literacy and financial application. Upon completion of the training, MSME participants gained a deeper understanding of the importance of financial literacy, financial reporting and the use of technology in financial reporting. This training makes increased awareness can provide significant benefits for MSME actors, especially by strengthening financial strategy efforts and improving the welfare of MSME stakeholders.